Student Engagement in Project Based Learning Activities - Revana khatarina Salsadilla; Ikariya Sugesti; Sirniawati (Journal of English Language Learning, 2025)
This study aims to analyze student engagement through a project-based learning model in a seventh grade EFL classroom. This research used a qualitative approach with a case study method to gain an in-depth understanding of how students engage in learning activities when using the PjBL model, where data was collected through observation, open ended questions interviews, and documentation. The research participants consisted of 34 seventh grade students in a junior high school. The results showed that the use of project-based learning model in EFL classroom can provide significant learning engagement for students in English learning process. The PjBL model encourages students to play an active role in learning by involving them in meaningful and contextualized tasks. Project-based learning has been shown to enhance students' enthusiasm, boost their self-confidence, foster creativity, and strengthen both independent and collaborative learning abilities. This study recommends the application of project-based learning in EFL contexts, especially in an effort to improve students’ ability to speak and write in English.